Evaluating the effectiveness of anti-corruption agencies in five Asian countries: A comparative analysis. Issue 1 (5th January 2015) - Quah, Jon S. T.
Abstract : Purpose: – The purpose of this paper is threefold: first, to ascertain the levels of effectiveness of the anti-corruption agencies (ACAs) in China, Japan, Philippines, Singapore and Taiwan; second, to explain why some of these ACAs are more effective than others; and third, to suggest some policy recommendations for addressing their limitations. Design/methodology/approach: – This paper relies on three well-known international indicators to assess the perceived extent of corruption in the five countries. Similarly, their quality of governance is assessed by their total percentile rank on the World Bank's six governance indicators in 2013. Findings: – Singapore's Corrupt Practices Investigation Bureau is effective because of its government's political will and favorable policy context. The Philippines and Taiwan rely on ineffective multiple ACAs, which are inadequately staffed and funded, and compete with each other for limited resources. China's Central Commission for Discipline Inspection is ineffective because corrupt party members are disciplined and not prosecuted, and the political leaders use corruption as a weapon against their opponents. Japan's weak political will is reflected in its reluctance to address its structural corruption. This paper concludes with policy recommendations for enhancing the effectiveness of the ACAs in the five countries. Originality/value: – The comparative analysis of the effectiveness of the ACAs in the five Asian countries and the policy recommendations for addressing their limitations will be of interest to policy makers, scholars and anti-corruption practitioners.